2017
DOI: 10.1155/2017/1206015
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Effects of Norathyriol and Mangiferin on α-Glucosidase

Abstract: Norathyriol is a metabolite of mangiferin. Mangiferin has been reported to inhibit α-glucosidase. To the best of our knowledge, no study has been conducted to determine or compare those two compounds on inhibiting α-glucosidase in vitro and in vivo by far. In this study, we determined the inhibitory activity of norathyriol and mangiferin on α-glucosidase in vitro and evaluated their antidiabetic effect in diabetic mice. The results showed that norathyriol inhibited α-glucosidase in a noncompetitive manner with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 14 publications
1
21
0
Order By: Relevance
“…'Apple' exhibits the considerable potential to possibly delay the absorption of glucose via the inhibition of α-glucosidase enzyme. All mango cultivars exhibited inhibition type of non-completive inhibition which is accordance with that of the major active compound, mangiferin (Shi et al, 2017).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…'Apple' exhibits the considerable potential to possibly delay the absorption of glucose via the inhibition of α-glucosidase enzyme. All mango cultivars exhibited inhibition type of non-completive inhibition which is accordance with that of the major active compound, mangiferin (Shi et al, 2017).…”
Section: Discussionsupporting
confidence: 66%
“…Gallic acid can increase GLUT-4 translocation concomitant with enhance glucose uptake activity (Prasad et al, 2010). Mangiferin and its metabolite, norathyriol, have been determined for anti-diabetic effects by various mechanisms such as lowering blood glucose level, improvement the glucose utilization and insulin sensitivity by upregulation of the phosphorylation of AMPK (Aderibigbe et al, 1999, Imran et al, 2017, Shi et al, 2017.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it was also reported that corilagin (IC 50 = 1.231 mM) was active against tyrosinase [48]. Mangiferin was reported to exert a non-competitive inhibition of α-glucosidase [49]. The methanol and water extracts were selected for further biological assays based on the results of colorimetric analyses indicating a more promising phytochemical profile in terms of total phenols and antiradical activity.…”
Section: Resultsmentioning
confidence: 99%
“…The following compounds were prepared in this fashion. The α-glucosidase inhibitory activity of compounds 2a-h was evaluated in triplicates in a 96 well microplate following a protocol by Shi et al [24]. In a 96-well plate, α-glucosidase (20 µL of enzyme solution of 0.48 U/mL in 100 mM phosphate buffer of pH 6.8) was incubated with different concentrations (0-100 µM) of the test compounds (2a-h and acarbose as positive control) in DMSO at 37 • C, for 10 min.…”
Section: Typical Procedures For the Synthesis Of Compounds 2a-hmentioning
confidence: 99%